Der Satz über den reziproken Operator in den pseudogenormten Räumen - Deksnytė, M. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:М. Дексните. Теорема Банаха об обратной операции в псевдонормированных пространствахM. Deksnytė. Banacho teorema apie atvirkštinį operatorių pseudonormuotoje erdvėje